Preoperative Magnetic Resonance Imaging Radiomics for Predicting Early Recurrence of Glioblastoma - Wang, Jing; Yi, Xiaoping; Fu, Yan; Pang, Peipei; Deng, Huihuang; Tang, Haiyun; Han, Zaide; Li, Haiping; Nie, Jilin; Gong, Guanghui; Hu, Zhongliang; Tan, Zeming; et al. (Frontiers in Oncology, 2021)
Purpose: Early recurrence of glioblastoma after standard treatment makes patient care challenging. This study aimed to assess preoperative magnetic resonance imaging (MRI) radiomics for predicting early recurrence of glioblastoma. Patients and Methods: A total of 122 patients (training cohort: n = 86; validation cohort: n = 36) with pathologically confirmed glioblastoma were included in this retrospective study. Preoperative brain MRI images were analyzed for both radiomics and the Visually Accessible Rembrandt Image (VASARI) features of glioblastoma. Models incorporating MRI radiomics, the VASARI parameters, and clinical variables were developed and presented in a nomogram. Performance was assessed based on calibration, discrimination, and clinical usefulness. Results: The nomogram consisting of the radiomic signatures, the VASARI parameters, and blood urea nitrogen (BUN) values showed good discrimination between the patients with early recurrence and those with later recurrence, with an area under the curve of 0.85 (95% CI, 0.77-0.94) in the training cohort and 0.84 [95% CI, 0.71-0.97] in a validation cohort. Decision curve analysis demonstrated favorable clinical application of the nomogram. Conclusion: This study shows the potential usefulness of preoperative brain MRI radiomics in predicting the early recurrence of glioblastoma, which should help in personalized management of glioblastoma.